Genetic analysis for a shared biological basis between migraine and coronary artery disease. (June 2015) - Winsvold, Bendik S.; Nelson, Christopher P.; Malik, Rainer; Gormley, Padhraig; Anttila, Verneri; Vander Heiden, Jason; Elliott, Katherine S.; Jacobsen, Line M.; Palta, Priit; Amin, Najaf; de Vries, Boukje; Hämäläinen, Eija; et al.
Abstract : Objective: To apply genetic analysis of genome-wide association data to study the extent and nature of a shared biological basis between migraine and coronary artery disease (CAD). Methods: Four separate methods for cross-phenotype genetic analysis were applied on data from 2 large-scale genome-wide association studies of migraine (19, 981 cases, 56, 667 controls) and CAD (21, 076 cases, 63, 014 controls). The first 2 methods quantified the extent of overlapping risk variants and assessed the load of CAD risk loci in migraineurs. Genomic regions of shared risk were then identified by analysis of covariance patterns between the 2 phenotypes and by querying known genome-wide significant loci. Results: We found a significant overlap of genetic risk loci for migraine and CAD. When stratified by migraine subtype, this was limited to migraine without aura, and the overlap was protective in that patients with migraine had a lower load of CAD risk alleles than controls. Genes indicated by 16 shared risk loci point to mechanisms with potential roles in migraine pathogenesis and CAD, including endothelial dysfunction ( PHACTR1 ) and insulin homeostasis ( GIP ). Conclusions: The results suggest that shared biological processes contribute to risk of migraine and CAD, but surprisingly this commonality is restricted to migraine without aura and the impact is in opposite directions. Understanding the mechanisms underlying these processes and their opposite relationship to migraine and CAD may improve our understanding of both disorders.